2019
DOI: 10.1016/j.buildenv.2019.106329
|View full text |Cite
|
Sign up to set email alerts
|

Using personally controlled air movement to improve comfort after simulated summer commute

Abstract: People often feel uncomfortably warm and sweaty in their workspace after commuting there by walking or cycling in summer. This is because body heat stored during the commute takes a substantial time to dissipate. People complaining about this uncomfortable transition may cause operators to lower the thermostat setpoint, causing long-term overcooling and wasting energy. In addition, space cooling is slow, requiring minutes to take effect. This study addresses how to improve comfort in the transition by increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has also been found that a modest air speed significantly reduces a CO2 bubble that accumulates in a person's breathing zone under still air conditions in workstations [16]. Finally, higher air temperatures and air speeds have also recently been shown to be far more effective (compared to cooler temperatures and still-air) at restoring comfort to occupants who have just entered a space with elevated metabolic rate and stored body heat from walking [17,18]. Note that in each of these above cases the desirable air flows are isothermal, involving only the room air itself.…”
Section: Comfort Zones and Air Quality Effects Under Elevated Air Movmentioning
confidence: 99%
“…It has also been found that a modest air speed significantly reduces a CO2 bubble that accumulates in a person's breathing zone under still air conditions in workstations [16]. Finally, higher air temperatures and air speeds have also recently been shown to be far more effective (compared to cooler temperatures and still-air) at restoring comfort to occupants who have just entered a space with elevated metabolic rate and stored body heat from walking [17,18]. Note that in each of these above cases the desirable air flows are isothermal, involving only the room air itself.…”
Section: Comfort Zones and Air Quality Effects Under Elevated Air Movmentioning
confidence: 99%
“…These rooms could be adjacent, but with independent entrances, or connected through an intermediate door. The latter configuration allows researchers to continuously monitor participants' reactions when exposed to different controlled environmental conditions [48]. Eight of the external facilities have just one room, but the possibility to work with movable internal partitions is mentioned for four of them [38,41,43,44].…”
Section: Construction Detailsmentioning
confidence: 99%
“…However, the earlier versions of standards never permitted it without air control requirement of individual subject. This shows that there has been considerable understanding of occupant interaction with building attributes particularly used for ventilation effects (Aynsley, 2008(Aynsley, , 2005Cândido et al, 2010;Zhai et al, 2019;Kabanshi et al, 2019). Some recent studies (Wang et al, 2019;Zamani et al, 2019) have not used either of these approaches and used comfort simulation for producing climatic data useful in the development of thermal comfort model.…”
Section: International Scenario Of Research On Thermal Comfortmentioning
confidence: 99%